2017
DOI: 10.1371/journal.pone.0173731
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels in patients with Parkinson’s disease: A meta-analysis

Abstract: BackgroundLower serum uric acid (UA) levels have been reported as a risk factor in Parkinson’s disease (PD). However, the results have been inconsistent so far.ObjectivesThe aim of the present study was to clarify the potential relationship of uric acid with PD.MethodsComprehensive electronic search in pubmed, web of science, and the Cochrane Library database to find original articles about the association between PD and serum uric acid levels published before Dec 2015. Literature quality assessment was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 43 publications
8
61
1
3
Order By: Relevance
“…Our findings in plasma are consistent with past literature in other neurodegenerative disorders, where lower blood and brain levels of UA have been reported in PD, ALS, and Alzheimer's disease patients (Church and Ward, 1994;Constantinescu and Zetterberg, 2011;Chen et al, 2012;Crotty et al, 2017). In PD, correlations were observed between higher serum levels of UA and not only a lower risk of developing the disease but also a slower rate of disease progression (Schlesinger and Schlesinger, 2008;Paganoni and Schwarzschild, 2017;Wen et al, 2017). Interestingly, studies in PD have also reported differences in men and women, with one study showing correlations between serum UA levels and disease duration in patients with PD only in men (Andreadou et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings in plasma are consistent with past literature in other neurodegenerative disorders, where lower blood and brain levels of UA have been reported in PD, ALS, and Alzheimer's disease patients (Church and Ward, 1994;Constantinescu and Zetterberg, 2011;Chen et al, 2012;Crotty et al, 2017). In PD, correlations were observed between higher serum levels of UA and not only a lower risk of developing the disease but also a slower rate of disease progression (Schlesinger and Schlesinger, 2008;Paganoni and Schwarzschild, 2017;Wen et al, 2017). Interestingly, studies in PD have also reported differences in men and women, with one study showing correlations between serum UA levels and disease duration in patients with PD only in men (Andreadou et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Since these early observations, accumulating epidemiological studies, laboratory data, preclinical models, and early clinical trial results have provided substantial support for a neuroprotective role for UA and its potential as a disease biomarker for PD (Constantinescu and Zetterberg, 2011;Chen et al, 2012;Crotty et al, 2017). In particular, UA has been suggested as a promising biomarker of reduced risk and milder progression in PD (Schlesinger and Schlesinger, 2008;Paganoni and Schwarzschild, 2017;Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid was found to be significantly lower in PD patients compared to controls. No difference was found between the East and West cohorts …”
Section: Analytical Epidemiologymentioning
confidence: 82%
“…Проте сучасні дослідження демонструють, що сечова кислота може діяти як антиоксидант при хворобі Паркінсона (ХП) та інших нейродегенеративних захворюваннях [2]. Вона здійснює нейропротекторну дію за допомогою ефективної нетралізації радикалів кисню та азоту в сироватці крові та клітинах мозку [3]. За даними проспективних досліджень виявлено, що високий вміст сечової кислоти у сироватці крові знижував ризик розвитку ХП [4].…”
Section: вступunclassified